Fitnah dalam Al-Qur’an - Nuraini Nuraini; Husniyani Husniyani (TAFSE: Journal of Qur'anic Studies, 2021)
People generally know that defamation is a lie or accusation without a basis of truth. Such words or accusations are spread with the intent to discredit others, such as damaging a good name to the detriment of the honor of others. However, in Arabic, the meaning of defamation is different from what is understood by the general public, in Arabic, the meaning of defamation means tests and trials as well as the meaning of defamation in the Qur`an. This article will describe how the verses of the Qur`an explain about slander. In the Qur`an, defamation is mentioned 52 times in 30 chapters with various meanings according to the context of the verse. From the searching of the verses of defamation in general, it is found that there are 15 meanings of the word defamation in the Qur`an. The meanings of defamation are shirk, deception, murder, obstruction from the path of Allah, deviation, reason, decision, sin, pain, target, retribution, trial, punishment, burning, and insanity. Of the 15 meanings of the word defamation in the Qur`an, the meaning of defamation is not coherent with the understanding of Indonesian people on slander in general, which only means as spreading false news to tarnish someone's name. Masyarakat pada umumnya mengetahui bahwa fitnah merupakan perkataan bohong atau tuduhan tanpa dasar kebenaran. Perkataan atau tuduhan tersebut disebarkan dengan maksud untuk menjelekkan orang lain, seperti merusak nama baik sehingga merugikan kehormatan orang lain. Namun, dalam bahasa Arab makna fitnah berbeda dengan yang difahami oleh masyarakat pada umumnya, dalam bahasa Arab makna fitnah berarti ujian dan cobaan demikian juga makna fitnah dalam al-Qur`an. Tulisan ini akan menggambarkan bagaimana ayat-ayat al-Qur`an menjelaskan tentang fitnah. Dalam al-Qur`an, fitnah disebutkan sebanyak 52 kali dalam 30 surah dengan beragam makna sesuai dengan konteks ayat. Dari penelurusaran terhadap ayat-ayat fitnah secara garis besarnya didapati ada 15 makna kata fitnah dalam al-Qur`an. Makna-makna yang dimaksud adalah syirik, penyesatan, pembunuhan, menghalangi dari jalan Allah, kesesatan, alasan, keputusan, dosa, sakit, sasaran, balasan, ujian, azab, bakar, dan gila. Dari 15 makna kata fitnah dalam al-Qur`an ini, tidak ditemukan makna fitnah sama persis dengan apa yang difahami oleh masyarakat Indonesia pada umumnya, yang bermakna menyebar berita bohong untuk menjelekan nama seseorang.